Evidence of antiblockade in an ultracold Rydberg gas - Amthor, Thomas; Giese, Christian; Hofmann, Christoph S.; Weidemüller, Matthias (Physical review letters, 2010)
We present the experimental observation of the antiblockade in an ultracold Rydberg gas recently proposed by Ates et al. [Phys. Rev. Lett. 98, 023002 (2007)]. Our approach allows the control of the pair distribution in the gas and is based on a strong coupling of one transition in an atomic three-level system, while introducing specific detunings of the other transition. When the coupling energy matches the interaction energy of the Rydberg long-range interactions, the otherwise blocked excitation of close pairs becomes possible. A time-resolved spectroscopic measurement of the Penning ionization signal is used to identify slight variations in the Rydberg pair distribution of a random arrangement of atoms. A model based on a pair interaction Hamiltonian is presented which well reproduces our experimental observations and allows one to deduce the distribution of nearest-neighbor distances.